Section Commentary. Cultural, Social, and Linguistic Aspects of School Consultation - Shriberg, David; Little, Tiondra J.; McPherson, Casey (Handbook of Research in School Consultation: Empirical Foundations for Educational and Human Sciences: Third Edition, 2026)
This chapter provides commentary on the four chapters in the section on the cultural, social, and linguistic aspects of school consultation. In each case, the authors pose penetrating insights and highlight a need for more extensive literature utilizing the full spectrum of research methodologies. In this spirit, this chapter suggests that strong consultation in these topical domains might be guided by the questions: (a) What is our mindset as researchers?, (b) Is the researcher culturally humble?, and (c) What might be most helpful? Building off the “what might be helpful” question, the commentary closes by framing two relevant areas where consultation research is lacking-consultation research in support of multiracial students and consultation research to address antisemitism and support Jewish students-as ways to expand the cultural, social, and linguistic aspects of school consultation literature. © 2026 selection and editorial matter, S. Andrew Garbacz, Daniel S. Newman, William P. Erchul, and Susan M. Sheridan; individual chapters, the contributors.
Keywords: dept.csp

The Neurospicy Queer Experience: Insights Into the Lived Experiences & Counseling Needs of Transgender and Gender Expansive Adults with ADHD - Gorski, J.; Bonjo, L.; Sassu, Kari; Councilor, KC (Journal of LGBTQ Issues in Counseling, 2026)
Keywords: ADHD; Expansive; Human sexuality; Lived experience; Qualitative research; Queer; Transgender; dept.com; dept.csp; gender affirming care; gender expansive; neurodivergence; neuroqueer; neurospicy

Professional involvement - Foss-Kelly, Louisa L.; Moorhead, Holly Hartwig (A Guide to Graduate Programs in Counseling: Second Edition, 2025)
Entering a counselor education program is just the first step in becoming a Professional Counselor, which includes developing a solid Professional Counselor identity and a plan for a fulfilling career. In this chapter, the authors provide a step-by-step plan for understanding key elements of becoming a Professional Counselor, beginning to work as a Professional Counselor, and contributing to the counseling profession. These activities include professional involvement, service, and scholarship as well as other meaningful pursuits for building one's successful career. The authors present a professional involvement pyramid to illustrate how Counselors can engage in professional identity development from graduate school throughout their careers. © Oxford University Press 2025. All rights reserved.
Keywords: Counseling; Counselor education; Professional Counselor; Professional Counselor identity; Professional development; Professional service; dept.csp

Service-Learning as a Mechanism to Prepare School Psychology Graduate Students: A Case Example. - McPherson, Casey; Karahalios, Vicky; Shriberg, David (Trainers' Forum, 2017)
An ongoing challenge in the preparation of school psychologists, particularly in the first year of graduate training, is finding learning experiences that provide students with an opportunity to apply foundational skills, such as consultation and data-based decision-making, in a culturally responsive manner. Service-learning is a well-established teaching mechanism designed to address just this need, yet there is scant scholarship on ways to utilize this methodology in school psychology training. This manuscript describes a service-learning experience at an urban tutoring center in which first-year school psychology Ed.S. and Ph.D. students gathered agency-wide comprehensive academic screening data and provided targeted consultation support in the area of reading comprehension to identified fourth- through sixth-grade students and their tutors. Indicators of the positive impact of this work across stakeholder groups is provided.
Keywords: dept.csp

International adoption of the Second Step program: Moderating variables in treatment effects - Moy, Gregory; Polanin, Joshua R.; McPherson, Casey; Phan, Thuy-Vy (School Psychology International, 2018)
Second Step is a universal social-emotional learning program designed to decrease antisocial behaviors, increase prosocial behaviors, and increase knowledge about content curriculum. Given the international focus of using Second Step to improve social-emotional skills, it is especially important to provide an updated synthesis on the effect of the intervention. A single-program meta-analysis was completed in order to determine effects of participating in Second Step and to explore moderators of program effectiveness on prosocial and antisocial behavior outcomes as well as knowledge of emotions. Five moderators were explored, including (a) program saturation, (b) dependent variable source, (c) grade range, (d) metro area, and (e) geographical location. A combined total of 18,847 participants were included in the analysis of 27 studies. Results of the current study indicate that Second Step’s impact on students’ knowledge and attitudes of violence and violence prevention is much stronger than on increasing prosocial behavior or reducing antisocial behavior.
Keywords: dept.csp

Machine learning predictive models to guide prevention and intervention allocation for anxiety and depressive disorders among college students - Zhai, Yusen; Zhang, Yixin; Chu, Zhicong; Geng, Baocheng; Almaawali, Mahmood; Fulmer, Russell; Lin, Yung-Wei Dennis; Xu, Zhaopu; Daniels, Aubrey D.; Liu, Yanhong; Chen, Qu; Du, Xue (Journal of Counseling & Development, 2024)
College student mental health has been a critical concern for professional counselors. Anxiety and depressive disorders have become increasingly prevalent over the past decade. Utilizing machine learning, a subset of artificial intelligence (AI), we developed predictive models (i.e., eXtreme Gradient Boosting [XGBoost], Random Forest, Decision Tree, and Logistic Regression) to identify US college students at heightened risk of diagnosable anxiety and depressive disorders. The dataset included 61,619 students from 133 US higher education institutions and was partitioned into a 90:10 ratio for training and testing the models. We employed hyperparameter tuning and cross-validation to optimize model performance and examined multiple measures of predictive performance (e.g., area under the receiver operating characteristic curve [AUC], accuracy, sensitivity). Results revealed strong discriminative power in our machine learning predictive models with AUC of 0.74 and 0.77, indicating current financial situation, sense of belonging on campus, disability status, and age as the top predictors of anxiety and depressive disorders. This study provides a practical tool for professional counselors to proactively identify students for anxiety and depressive disorders before these conditions escalate. Application of machine learning in counseling research provides data-driven insights that help enhance the understanding of mental health determinants, guide prevention and intervention strategies, and promote the well-being of diverse student populations through counseling.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/jcad.12543
Keywords: anxiety; depression; dept.csp; machine learning; peer-reviewed; predictive model; prevention and early intervention

Crashing Waves Activity - Foss, Louisa L (Treating Those with Mental Disorders: A Comprehensive Approach to Case Conceptualization and Treatment, 2014)
Note: This is the bound book only and does not include access to the Enhanced Pearson eText. To order the Enhanced Pearson eText packaged with a bound book, use ISBN 0133834255.Treating Those with Mental Disorders: A Comprehensive Approach to Case Conceptualization and Treatment is the authoritative reference on selecting and applying treatments for use in counseling and treating those with mental disorders. In it, students and new counselors don’t just learn about the clinical issues, the DSM-5 system of diagnosis, and interventions that can be used in counseling and treating those with mental disorders, they see clearly how to proceed in treatment planning and how to implement treatment approaches and interventions. The authors present a conceptual framework model, I CAN START, which consists of case conceptualization components and addresses treatment planning from a strength-based, contextually sensitive perspective. Case studies; creative Clinical Toolboxes; Voices from the Trenches; a comfortable presentation of the material; and a comprehensive, rigorous assimilation of the current treatment literature combine to empower counselors to thoughtfully and deliberately help their clients tackle their complex issues and difficulties. The Enhanced Pearson eText features Case studies, creative Clinical Toolboxes, and Voices from the Trenches which present real-life examples of critical counseling concepts and approaches.Improve mastery and retention with the Enhanced Pearson eText* The Enhanced Pearson eText provides a rich, interactive learning environment designed to improve student mastery of content. The Enhanced Pearson eText is:Engaging. The new interactive, multimedia learning features were developed by the authors and other subject-matter experts to deepen and enrich the learning experience. Convenient. Enjoy instant online access from your computer or download the Pearson eText App to read on or offline on your iPad® and Android® tablet.* Affordable. The Enhanced Pearson eText may be purchased stand-alone or with a loose-leaf version of the text for 40-65% less than a print bound book. *The Enhanced eText features are only available in the Pearson eText format. They are not available in third-party eTexts or downloads.*The Pearson eText App is available on Google Play and in the App Store. It requires Android OS 3.1-4, a 7” or 10” tablet, or iPad iOS 5.0 or later.
Keywords: dept.csp

Socioeconomic Status - Foss-Kelly, Louisa; Baycroft, Jessica (The SAGE Encyclopedia of Marriage, Family, and Couples Counseling, 2017)
Keywords: dept.csp

Poverty and Family Develoment - Foss-Kelly, Louisa; Rand, Arden G. (The SAGE Encyclopedia of Marriage, Family, and Couples Counseling, 2017)
Keywords: dept.csp

Growing grassroots: counseling student experiences in legislative professional advocacy - Foss-Kelly, L.L.; Parzych, J.; Feshler, M.; Yale, J.; Chen, Q. (Journal of Counselor Leadership and Advocacy, 2024)
Counselor educators and supervisors have a vital role in promoting legislative professional advocacy (LPA). An interpretative qualitative analysis study of counseling graduate students involved in state-level LPA was conducted. Findings revealed six distinct themes: (1) professional counselor identity, (2) knowledge, attitudes and skills, (3) professional support, (4) power of the group, (5) social justice, and (6) personal impact. Study findings may help counselor educators and supervisors educate, guide, and mentor students, thereby increasing the likelihood of professional counselor LPA. © 2024 Chi Sigma Iota.
Keywords: Counselor education and supervision; counselor advocacy; dept.csp; legislative professional advocacy; professional identity

Making Choices and Reducing Risk (MCARR): School Counseling Primary Prevention of Substance Use - Foss-Kelly, Louisa L.; Generali, Margaret M.; Crowley, Michael J. (Professional Counselor, 2021)
The consequences of adolescent drug and alcohol use may be serious and far-reaching, forecasting problematic use or addictive behaviors into adulthood. School counselors are particularly well suited to understand the needs of the school community and to seamlessly deliver sustainable substance use prevention. This pilot study with 46 ninth-grade students investigates the impact of the Making Choices and Reducing Risk (MCARR) program, a drug and alcohol use prevention program for the school setting. The MCARR curriculum addresses general knowledge of substances and their related risks, methods for evaluating risk, and skills for avoiding or coping with drug and alcohol use. Using a motivational interviewing framework, MCARR empowers students to choose freely how they wish to behave in relation to drugs and alcohol and to contribute to the health of others in the school community. The authors hypothesized that the implementation of the MCARR curriculum would influence student attitudes, knowledge, and use of substances. Results suggest that the MCARR had a beneficial impact on student attitudes and knowledge. Further, no appreciable increases in substance use during the program were observed. Initial results point to the promise of program feasibility and further research with larger samples including assessment of longitudinal impact.
0 citations (Crossref) [2023-10-31] ERIC Number: EJ1312406
Keywords: Adolescents; Counselor Role; Decision Making; Grade 9; Health Behavior; High School Students; Knowledge Level; Prevention; Program Effectiveness; Risk; School Counseling; School Counselors; Student Attitudes; Substance Abuse; Urban Schools; dept.csp; peer-reviewed

Behavior Management: Traditional and Expanded Approaches - Haynes, Norris M. (University Press of America, 2013)
This book serves as a reference guide on the implementation of basic and more advanced behavior management strategies. It covers the principles and application of basic learning theories as well as those that integrate cognitions and emotions in treatment frameworks. It takes the reader through the essential steps in developing behavior management plans, including conducting functional behavior analyses and curriculum-based assessments. The contributors describe and share examples of various behavioral intervention techniques that address behavioral challenges in a variety of settings. These methods include more traditional approaches, such as classical and instrumental learning strategies and cognitive behavior management techniques. They also discuss less traditional and alternative approaches, including social and emotional learning, character development, and yoga. The book is appropriate for professionals in various specialty areas, including classroom teachers, college professors, and undergraduate and graduate students majoring in general education, special education, school psychology, psychology, educational leadership, school counseling, and social work. It is also appropriate for professionals who work with children on the autism spectrum and for board certified behavioral analysts.
Keywords: Education; Human behavior; Teaching; Individualized instruction; Problem children; dept.csp

Clinical Interviewing and Counseling Skill Development: Global Perspectives on Client Change - Nwachuku, Uchenna T. (Linus Publications, 2013)
Keywords: Interviewing in mental health; Interviewing in psychiatry; dept.csp; faculty_collection

Group Dynamics: Basics and Pragmatics for Practitioners - Haynes, Norris M. (University Press of America, 2012)
Keywords: Social groups; Group facilitation; dept.csp; dept.eco; faculty_collection

School Counselors Share Their Favorite Group Activities: A Guide to Choosing, Planning, Conducting, and Processing - Foss, Louisa L.; Association for Specialists in Group Work (Association for Specialists in Group Work, 2008)
Keywords: Educational counseling; Group counseling for children; Group counseling for teenagers; Activity programs in education; dept.csp; faculty_collection

Understanding and Responding to Affectional and Transgender Prejudice and Victimization - Viehl, C.; Ginicola, M.M.; Ellis, A.; Charette, R.J. (Trauma Counseling Theories and Interventions for Managing Trauma, Stress, Crisis, and Disaster: Second Edition, 2022)
In addition to traumas that heterosexual and cisgender people experience, queer and transgender people face a heterosexist and cissexist culture, in which marginalization and trauma against them is normalized or minimized. In this chapter, the experience of hate crimes and violence, relational and interpersonal trauma, religious based-trauma, and sociocultural and political-based trauma are covered in relation to how it impacts Lesbian, Gay, Bisexual, Trans, and Queer (LGBTQ) people. Clinical and counseling implications are discussed. The increase in mental health challenges is explained via the minority stress model. Implications for diagnosis and trauma-informed practices for queer and transgender people are discussed. Additionally, the role of the mental health professional as a social justice advocate is explored, including how social justice frameworks can be incorporated in the counseling environment. © 2023 Springer Publishing Company, LLC and 2012. All rights reserved.
Keywords: dept.csp

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pits.22757
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race

Counseling people living in poverty: The CARE model - Foss, L.L.; Generali, M.M.; Kress, V.E. (Journal of Humanistic Counseling, 2011)
Counselors frequently counsel clients who live in poverty. The authors describe the new CARE model that addresses the influence of multiple systems on poor clients' experiences. A social justice, humanistic intervention, the CARE model emphasizes cultivating a positive counseling relationship with poor clients, empathizing with their unique realities, and working to remove barriers to future success and well-being by building on their strengths. © 2011 by the American Counseling Association.
7 citations (Crossref) [2023-10-31]
Keywords: dept.csp

Assessment - Foss-Kelly, L. (Values and Ethics in Counseling: Real-Life Ethical Decision Mak., 2013)
Journal Abbreviation: Values and Ethics in Counseling: Real-Life Ethical Decision Mak.
Keywords: dept.csp

Evaluation, assessment, and interpretation: Assessment - Foss-Kelly, L. (Values and Ethics in Counseling: Real-Life Ethical Decision Mak., 2013)
Journal Abbreviation: Values and Ethics in Counseling: Real-Life Ethical Decision Mak.
Keywords: dept.csp

New counselors' experiences of community health centers - Freadling, A.H.; Foss-Kelly, L.L. (Counselor Education and Supervision, 2014)
This phenomenological study explored 6 new counselors' experiences working in community mental health centers and their experiences of the Council for Accreditation of Counseling and Related Educational Programs-accredited training received in preparation for such work. Three themes from the interviews were identified to provide implications for counselor preparation: contextual descriptions, essential graduate training components, and supportive factors. © 2014 by the American Counseling Association. All rights reserved.
7 citations (Crossref) [2023-10-31]
Keywords: community mental health; counselor education; dept.csp

Couples: Case - Ginicola, M.M. (Critical Incidents in Integrating Spirituality into Counseling, 2015)
This chapter talks about Michael and Ethan's case study, where two people were involved in being in an interfaith relationship. The author's primary goal was to help each become empathic and to understand the other's position on coming out and being a public couple. A secondary goal was to increase their communication in articulating their feelings surrounding coming out officially. Working from an existential approach, the author encouraged them both to explore their meanings associated with religion, their families, and each other. He used the Emotionally Focused Couples Therapy (EFCT) approach, and insights of integrating sexual orientation and religious identities, spiritual interventions, and dealing with discrimination. Building on the strength-based model, the author identified positive assets that each brought to the relationship individually and in a partnership. Each was willing to develop a plan that represented a middle ground between their two positions. © 2015 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Crit. Incid. in Integr. Spirit. into Couns.
Keywords: Discrimination; Emotionally Focused Couples Therapy; Homosexuality; Religious identities; Same-sex couples; Spiritual Interventions; dept.csp

Military Families: Case - Smith, C. (Critical Incidents in Integrating Spirituality into Counseling, 2015)
This chapter discusses the case of Kelly, a 43-year-old white woman married to an Air Force pilot, came to counseling because she was struggling with several issues. Watching the news about and receiving updates from her husband's command exacerbated Kelly's sense of being overwhelmed and powerless. The author first tried to identify the supports Kelly needed to have in place as she went through her lumpectomy. Second, the counselors explored how to secure resources for James's school issues. According to the author, family counseling sessions should be conducted once Kelly begins to make some minor adjustments and feels more in control. Other possible approaches include solution-focused interventions for short-term results, cognitive-behavioral therapy with Kelly and the children, and family systems theory. As religion is important to Kelly and her husband, the counselor could explore ways to incorporate interventions appropriate to her religious beliefs and values. © 2015 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Crit. Incid. in Integr. Spirit. into Couns.
Keywords: Cognitive-behavioral therapy; Family counseling sessions; Family systems theory; Military families; Religious interventions; Spiritual resources; dept.csp

Counseling Transgender Clients - Brammer, R.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The issues surrounding working with clients who experience a disconnect between their gender identity and their designated sex at birth are discussed. Gender and gender identity terminology are thoroughly discussed, including terminology that should be avoided. The complex issues surrounding terminology, gender, and changing terms are explored. The cultural history of third gender people, as well as the impacts of colonization, are discussed. Authors also present the prevalence and identity development of transgender persons. Transgender persons face a significant risk of experiencing bias incidents, indicating a significant increase in minority-based stress. Focusing specifically on transgender persons who wish to transition, the authors explore physical and mental health challenges that clients may face. Special considerations with the DSM and use of the Gender Dysphoria diagnosis, are explained. Affirmative counseling strategies, including preparation and counseling practices, with transgender persons are examined. Special attention is given to intersectional issues, such as age and ethnicity. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: ALGBTIC competencies; Affirmative counseling; Gender identity; Identity development; Intersectionality; LGBT; Mental health; Minority stress; Physical health; Third gender; Transgender; dept.csp

Counseling an LGBTQI+ Person of Color - Filmore, J.M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The intersectionality of ethnicity and affectional orientation is discussed within this chapter, with special attention given to specific challenges faced by queer people of color (QPOC). Four elements of African American culture that may negatively impact queer-identified persons are: heterosexism, masculinity, issues surrounding HIV, and the role of the Black Church. In Latin Americans, concepts of machismo and marianismo, Catholicism, familismo, and respeto, are discussed in terms of their impact on LGBTQI+ persons. Authors also discuss elements of Asian culture that will impact queer-identified Asians: stigma, complementarity, collectivism and conformity, and shame. The importance of culture specific counseling is underscored. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: African American; Asian American; Hispanic; Intersectionality; LGBT; Latin American; Queer person of color; dept.csp

Counseling Intersex Clients - Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Persons who are born with ambiguous or a combination of both male and female genitalia are referred to as intersex. The biological nature of intersex conditions, or disorders/differences of sex development, are reviewed in this chapter. Issues of bias for people who are intersex are discussed, as children are often made to feel abnormal and required to keep their difference a secret. Parents and families may also experience mental health symptoms, such as traumatic reactions, at their child's birth, when a gender cannot readily be assigned to their child. Although, doctors have (and some still continue) to recommend genital surgery without the child's consent, this is considered unethical by many advocacy organizations for intersex people. Physical issues and the standard of care recommended by advocacy organization and ALGBTIC are discussed. The role of a counselor working with a family with an intersex infant is discussed, as are specific counseling techniques for working with intersex clients of all ages. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: ALGBTIC competencies; Affirmative counseling; Difference of sex development; Disorders of sex development; Intersex; LGBT; dept.csp

Counseling Two-Spirit Clients - Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The term two-spirit refers to persons who identify as indigenous to the Americas and as having a gender and/or affectional variance. Historically recognized by most Native tribes, two-spirit persons were seen as a blessing to their tribe, having high social and spiritual value. Native spirituality and the history of two-spirit persons are explored within this chapter. Because of colonization, much of these traditional beliefs have been lost or distorted, leaving LGBTQI+ people within Native communities experiencing high levels of bias and abuse. Increased physical and mental health challenges due to these significant minority stressors are discussed. Specific counseling skills and techniques for working with this population are explored. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Affirmative counseling; LGBT; Native american; Queer person of color; Two-spirit; dept.csp

The Science of Gender and Affectional Orientation - Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Sex, gender, and affectional orientation are complex issues; scientific research has long investigated the etiology of gender variance and affectional orientation. Although some interpret this research as contributing to a viewpoint of LGBTQI+ as abnormal, biological research can also be viewed as a confirmation of the natural human variance and adaptability that different gender identities and affectional orientation serves. Research supporting a biological basis for sexual attraction, gender identity, and affectional orientation is presented. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Affectional orientation; Etiology; Gender identity; Gender variance; LGBT; Science; dept.csp

Physical and Mental Health Challenges Found in the LGBTQI+ Population - Ginicola, M.M.; Filmore, J.M.; Smith, C.; Abdullah, J. (Affirmative Counseling With LGBTQI+ People, 2017)
LGBTQI+ people face significant increased stress and marginalization surrounding their gender and/or affectional identities. The minority stress model (Meyer, 2003) serves as a helpful framework when understanding negative coping behaviors, and poor physical and mental health. Microaggressions, marginalization, discrimination, abuse, harassment, and experience of bias incidents all add to the LGBTQI+ person's stress. Intersectional identities may exponentially increase this stress, as is the case for queer persons of color. Authors consider general physical health and mental health risks for lesbian, gay male, bisexual, and transgender clients. Barriers to quality health care and protective factors are also covered. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Intersectionality; LGBT; Mental health; Minority stress; Physical health; dept.csp

Working With LGBTQI+ Clients Who Have Experienced Religious and Spiritual Abuse Using a Trauma-Informed Approach - Ginicola, M.M.; Filmore, J.M.; Stokes, M. (Affirmative Counseling With LGBTQI+ People, 2017)
Many LGBTQI+ clients have been explicitly harmed by religious leaders and those using religious doctrine. This experience can go beyond discrimination and oppression; a person may have experienced serious emotional and spiritual abuse at the hands of faith practitioner attempting to condemn affectional orientation and/or gender identity variance in order to comply with religious doctrine. The current religious conflict with LGBTQI+ issues is briefly reviewed. Authors define and explore spiritual abuse, as well as the experience of spiritual abuse as experienced by a LGBTQI+ person. Counseling challenges and strategies are described. Specifically, the use of a trauma informed counseling approach as applied to clients who have experienced spiritual abuse is explored. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Affirmative counseling; Counseling techniques; LGBT; Religion; Religious trauma; Spiritual abuse; Spirituality; Trauma informed approach; dept.csp

The Role of Religion and Spirituality in Counseling the LGBTQI+ Client - Ginicola, M.M.; Furth, B.H.; Smith, C. (Affirmative Counseling With LGBTQI+ People, 2017)
When religion or spirituality is present, it likely impacts the needs a LGBTQI+ person may bring to counseling. First, the LGBTQI+ person's identity development is likely altered in significant ways, either positively or negatively. Research on this topic is reviewed and the FAITH model for working with LGBTQI+ clients struggling with their faith is presented. Ethical issues arising between disaffirming religious beliefs and counseling LGBTQI+ clients are also reviewed. Authors review affirming and semi-affirming religious organizations within the United States. Additional counseling issues are also explored. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Affirmative counseling; Affirming religions; Counseling; Ethics; LGBT; Religion; Spirituality; dept.csp

Counseling Asexual Clients - Ginicola, M.M.; Ruggiero, A. (Affirmative Counseling With LGBTQI+ People, 2017)
Asexual persons experience little to no sexual attraction to others, although they may still experience romantic attraction and a desire to bond with others. Asexual people often experience bias and marginalization from allosexuals (persons who experience sexual attraction) within heterosexual and queer communities. Asexuals may also face bias from well-intentioned therapists who assume their lack of sexual attraction is due to trauma or a disorder. Although little research has been performed on counseling asexual persons, the authors review appropriate diagnostic counseling criteria for arousal and sexual disorders versus an asexual identity, and affirmative and strength-based techniques appropriate for work with this population. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: ALGBTIC competencies; Affirmative counseling; Asexual; LGBT; dept.csp

Counseling Gay Male Clients - Ginicola, M.M.; Sanabria, S.; Filmore, J.M.; DeVoll, M. (Affirmative Counseling With LGBTQI+ People, 2017)
The issues surrounding working with gay men in counseling are reviewed within this chapter. Prevalence, identity development, and relationships are explored. Gay males experience a significant amount of bias and discrimination; they are the largest single target of hate crimes within the LGBTQI+ population reported to the FBI every year. This risk is greater when intersectional minority identities are also present; more gay males are targets for hate crimes when they present as gender non-conforming, are men of color, as well as live in a rural area of the country. Authors explore physical and mental health issues related uniquely to gay male clients, as a result of the heightened minority stress. Affirmative counseling techniques for working with gay male clients is reviewed, with special attention given to developing counselor self-awareness, developmental counseling, and empowerment strategies. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: ALGBTIC competencies; Affirmative counseling; Counseling techniques; Gay male; Identity development; Intersectionality; LGBT; Mental health; Minority stress; Physical health; dept.csp

Developing Competence in Working With LGBTQI+ Communities: Awareness, Knowledge, Skills, and Action - Ginicola, M.M.; Smith, C.; Filmore, J.M. (Affirmative Counseling With LGBTQI+ People, 2017)
When providing counseling to a LGBTQI+ client, counselors must understand their ethical obligations, as well as attend to the multiple sets of counseling competencies. Using a multicultural and social justice counseling framework, counselors can situate their learning into very specific areas for LGBTQI+ clients: self-awareness of attitudes and beliefs, knowledge of issues faced by LGBTQI+ people, counseling skills, and action. Understanding common terminology, the history of the LGBTQI+ population, and modern issues faced by these communities can help lay the foundation for counselors working with LGBTQI+ persons. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Affirmative counseling; LGBT; LGBTQI+ clients; Multicultural counseling; Social justice; dept.csp

Preface - Ginicola, M.M.; Smith, C.; Filmore, J.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Keywords: dept.csp

Evidence-Based Practice for Counseling the LGBTQI+ Population - Goodrich, K.M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Authors review the current state of Evidence Based Practice (EBP) for counseling LGBTQI+ clients. Although there is an identified need for more research in this area, the research supports a general affirmative approach. Strategies for building rapport, assessment, and interventions are reviewed. Specific attention is given to the importance of cultural accommodations and adaptations of EBPs that have not been tested directly on the LGBTQI+ population. Authors also explore how integrative and creative therapies may hold helpful strategies for work with these communities. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Affirmative counseling; EBP; Empirically based practice; Evidence based practice; LGBT; dept.csp

Identity Development, Coming Out, and Family Adjustment - Goodrich, K.M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
LGBTQI+ youth face an identity struggle that is dissimilar to their heterosexual and/or cisgender peers. While family and community acceptance impacts the process of understanding one's own affectional orientation and/or gender identity, all LGBTQI+ persons typically engage in a process of understanding and eventually accepting their affectional and/or gender variance. The authors review LGBTQI+ Identity Formation Models, as well as the influence of intersectionality on identity. The benefits and challenges of coming out are explored, as counselors need to understand this delicate process and how to support clients who are considering coming out. Counselor work with families is also reviewed. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Coming out; Family; Identity development; Intersectionality; LGBT; LGBT youth; dept.csp

Counseling Bisexual/Pansexual/Polysexual Clients - Harper, A.J.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
The issues surrounding working with clients who are predisposed to share affection with people from more than one gender. Terminology, as well as prevalence are discussed. Bisexual identity development and relationships are explored. Experiences of bias, including bisexual erasure, biphobia, and bisexual invisibility are discussed. Bisexuals may encounter monosexism and marginalization in both heterosexual and queer communities, among people who do not identify with non-binary identities. Intersectional identities can be subject to increased oppression. Authors explore how minority stress contributes to greater physical and mental health issues in bisexual clients. Although there has been little research on affirmative counseling techniques for bisexual clients, a general strength-based approach with feminist and social justice techniques is recommended. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: ALGBTIC competencies; Affirmative counseling; Bisexual; Identity development; Intersectionality; LGBT; Mental health; Minority stress; Pansexual; Physical health; Polysexual; dept.csp

LGBTQI+ Persons in Adulthood - Moore-Ramirez, A.; Kautzman-East, M.; Ginicola, M.M. (Affirmative Counseling With LGBTQI+ People, 2017)
Due to their stigmatizing and marginalized experiences, as adults, LGBTQI+ people have variant developmental experiences for identity and intimacy. Their collegiate and occupational experiences may also be impacted by these negative experiences surrounding their LGBTQI+ identity. Experiences within the military are also covered within this chapter. The authors also discuss mid-life experiences for those within the LGBTQI+ population, including relationships, marriage, family planning and raising children. Issues facing the LGBTQI+ elderly population are also covered. © 2017 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Affirm. Couns. With LGBTQI+ People
Keywords: Adulthood; Career; College; Development; Elderly; LGBT; dept.csp

Addressing students' social and emotional needs: the role of mental health teams in schools. - Haynes, Norris M (Journal of health & social policy, 2002)
Children in today's society face many stresses from a variety of sources that have a major impact on thier psychosocial adjustment and academic performance in school. These stressful events and thier consequences on the quality of life and academic success are particularly significant among low-income and ethnic minority students in American society. Many schools have adopted strategies to help students who are impacted by stressful life events to deal affectively with their problems in an attempt to reduce school failure and school dropout rates among these students. Most notable among these strategies are school-based mental health programs including the establishment of school-based mental health teams which seek to proactively address individual student concerns while improving the general climate of schools. The evidence seems to support the claim that these school-based services have a positive impact on students' social and emotional well-being as well as on their academic achievements. However, with more careful monitoring and much more consistent support from administrators and policy makers, these school-based approaches can more fully realize their potential to enhance the quality of life and to positively impact the future of many poor and ethnic minority students.
33 citations (Crossref) [2023-10-31] Place: United States Haynes, Norris M. Center for Community and School Action Research, Southern Connecticut State University, USA.
Keywords: *Mental Health Services/og [Organization & Administration]; *Patient Care Team; *School Health Services/og [Organization & Administration]; *Social Support; *Stress; Psychological/th [Therapy]; Adolescent; Child; Children's mental health; Female; Humans; Male; Minority mental health; School-based mental health; Social Problems; Social Work; Psychiatric; Social and emotional learning; Socialization; Student health; Teaching/mt [Methods]; United States; academic achievement; child; child care; dept.csp; emotional stability; ethnic group; health care need; human; life event; lowest income group; mental health; mental health service; policy; quality of life; review; school health service; social learning; social policy; social psychology; student; wellbeing

An exploration of themes that influence the counselor education doctoral student experience. - Protivnak, Jake J; Foss, Louisa L (Counselor Education and Supervision, 2009)
The purpose of the present study was to explore the themes that counselor education doctoral students perceive as influencing their experience. The results of an exploratory qualitative study in which counselor education doctoral students provided their perceptions of what helped or hindered their progress are presented. Themes identified as both positively and negatively influencing their experiences were departmental culture, mentoring, academics, support systems, and personal issues. Recommendations are provided for counselor educators to consider in their work with doctoral students. © 2009 by the American Counseling Association. All rights reserved.
48 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/141-404-873-290-857 tex.type: [object Object]
Keywords: dept.csp

Social competence, social support, and academic achievement in minority, Low-Income, urban elementary school children - Elias, Maurice J; Haynes, Norris M (School Psychology Quarterly, 2008)
Despite living in disadvantaged urban communities experiencing social and economic hardships, many children emerge with positive outcomes. Social-emotional competence and social support were hypothesized to have strong influences on academic trajectories during the critical period of academic skill acquisition. Participants were 282 third-grade students from six elementary schools in a Northwestern urban community. Beyond the importance of prior levels of academic competence, considerable variance in end-of-year academic outcomes was predicted by initial levels of academic social-emotional competence and improvements in social-emotional competence and perceived teacher support over the course of the year. Noteworthy is that findings were strongest for African-American students, but methodological caveats regarding research with underachieving minority youth were discussed. The findings suggest that school psychologists and others designing interventions to improve achievement of disadvantaged students should address social-emotional competencies and classroom climate, especially teacher support of students.
170 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-548-958-283-276 tex.type: [object Object]
Keywords: academic underachievement; dept.csp; prevention; resilience; social-emotional competence; urban minority youth

Mind-body health in the school environment - Bray, Melissa A; Maykel, Cheryl (International Journal of School and Educational Psychology, 2016)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/026-180-143-210-553 tex.type: [object Object]
Keywords: dept.csp

Thinking in new ways and in new times about reading - Leu, Donald J; Maykel, Cheryl (Literacy Research and Instruction, 2016)
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-033-594-976-852 tex.type: [object Object]
Keywords: dept.csp

Love thy neighbor: A guide for implementing safe school initiatives for LGBTQ students in nonaffirming religious communities - Ginicola, Misty M; Smith, Cheri; Rhoades, Elizabeth (Journal of LGBT Issues in Counseling, 2016)
Although setting up a safe school is an important task for a school counselor, his or her efforts may be resisted when attempting to develop a safe school initiative in a religious community; for example, one conservative-based website gives parents explicit instructions on how to fight a school's safe schools initiatives. This article provides a review of the issues involved and a specific framework for school counselors who wish to set up a Safe Schools Initiative in the context of a resistant atmosphere, using a social justice framework. © 2016 Taylor & Francis Group, LLC.
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/101-808-473-793-033 tex.type: [object Object]
Keywords: LGBTQ; dept.csp; religious conflict; safe schools; school counseling; social justice

Psychologically based therapies to improve lung functioning in students with asthma. - Maykel, Cheryl; Bray, Melissa A; Gelbar, Nicholas W; Caterino, Linda C; Avitia, Maria J; Sassu, Kari; Root, Melissa M (International journal of school and educational psychology, 2016)
Asthma is a common, chronic respiratory disease that can be costly to both society and the individual. In addition to increased absenteeism, children with asthma may also be at a greater risk for developing comorbid anxiety and depression. Various complementary psychological treatments have been effective at reducing both asthmatic symptoms and psychological distress. Although the research in the area of mind-body treatments as it pertains specifically to persons with asthma is still developing, this article will describe several promising alternative treatment methods, many of which have already been, or could be easily be applied for use in a school setting. © 2016, © 2016 International School Psychology Association.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-833-211-583-544 tex.type: [object Object]
Keywords: art therapy; asthma; biofeedback; dept.csp; hypnosis; mind-body; mindfulness; music therapy; relaxation and guided imagery; school-based interventions; written emotional expression; yoga

Students with cancer: presenting issues and effective solutions. - Root, Melissa M; Bray, Melissa A; Maykel, Cheryl; Cross, Karen; Shankar, Nilani L; Theodore, Lea A (International Journal of School and Educational Psychology, 2016)
Practitioners working with children diagnosed with cancer in the school environment must consider several facets in order to effectively work with the child and family. The remission rate for children with cancer is relatively high, so one must consider whether the child is anticipating treatment, actively in treatment, or posttreatment when one thinks about the potential stressors and cognitive impacts of cancer on the child's education. This article focuses on facts associated with childhood cancer that are relevant to school-based practitioners, common stressors for children and adolescents with a personal cancer diagnosis in their lives, research-based interventions, and accommodations and modifications to consider. © 2016, © 2016 International School Psychology Association.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/117-223-995-782-603 tex.type: [object Object]
Keywords: accommodations; adolescent cancer; childhood cancer; dept.csp; evidence-based practices; intervention; modifications; pediatric oncology; school psychologist

Financial health and mental health among clients of a community mental health center: making the connections - Harper, Annie; Clayton, Ashley; Bailey, Margaret; Foss-Kelly, Louisa; Sernyak, Michael J.; Rowe, Michael (Psychiatric Services, 2015)
Objectives: This study evaluated financial challenges, satisfaction with financial-management supports, and interest in additional or alternative supports among clients of a mental health center. Methods: Six focus groups were held with 39 clients of an urban community mental health center who reported having difficulty with their finances. Five focus groups were held with direct-care staff who provided services to the clients. Investigators used an inductive analytical approach to distill themes from notes taken during the focus groups. Results: Clients emphasized the challenges of living in poverty and described using complex strategies to sustain themselves, including negotiating benefits systems, carefully planning purchases, and developing and relying on social relationships. They spoke of having uneven access to tools and services for managing their money, such as advice from direct-care staff, representative payees, and bank accounts, and had varying opinions about their value. Noting concerns similar to those of clients, direct-care staff expressed frustration at the lack of support services for helping clients manage their finances. Both clients and staff expressed the need for more services to help clients with their finances. Conclusions: Findings suggest a need for more services to support people with mental illness to manage their finances, particularly a more flexible and broader range of options than are provided by current representative-payee mechanisms.
17 citations (Crossref) [2023-10-31] tex.eissn: 1557-9700 tex.unique-id: ISI:000370847300012
Keywords: Article; Community Mental Health Centers; Connecticut; Focus Groups; Humans; Mental Disorders; Mental Health; Patient Advocacy; Patient Satisfaction; Poverty; Social Support; Urban Population; adult; analytic method; clinical article; clinical assessment; clinical evaluation; community mental health center; coping behavior; dept.csp; economics; female; financial management; health care access; health insurance; human; information processing; interpersonal communication; male; managed care; medical staff; mental disease; mental health; mental health service; money; patient advocacy; patient satisfaction; poverty; social interaction; social support; treatment planning; urban population

The added value of the school of the 21st century when combined with a statewide preschool program. - Ginicola, Misty; Finn-Stevenson, Matia; Zigler, Edward (The American journal of orthopsychiatry, 2013)
Although schools have begun to employ multiple programs to reach educational goals, little attention has been paid to the efficacy of combining separate programs. The present study investigates the combination of a school reform model, the School of the 21st Century (21C), and the Arkansas Better Chance (ABC) program, where preschools apply for state funds to provide high quality services to children at risk. To determine if 21C adds anything to the ABC program, the present study compared results from a developmental assessment. The authors compared school-based preschools that had both ABC and 21C services to those programs that offered only ABC services. Results indicated that, at baseline, children within the 21C/ABC programs scored the same or poorer than their ABC-only counterparts. However, at the end of the year, participants at 21C/ABC preschools were significantly ahead of ABC-only programs on all developmental indicators. There were also differences favorable to 21C/ABC preschools between the programs' quality ratings as measured by the Early Childhood Environmental Rating Scale. Copyright © 2013 American Orthopsychiatric Association.
1 citations (Crossref) [2023-10-31] Place: United States Ginicola, Misty. Southern Connecticut State University, New Haven, CT 06511, USA. ginicolam2@southernct.edu
Keywords: *Early Intervention; Educational; *Schools; Arkansas; Arkansas Better Chance program; Child care; Child; Preschool; Early Intervention (Education); Educational Status; Family support; Female; Humans; Male; Poverty; Preschool children; School children; School readiness; Schools; The School of the 21st Century; article; child; dept.csp; education program; female; history; human; male; preschool child; rating scale; school

Counseling through images: using photography to guide the counseling process and achieve treatment goals - Ginicola, Misty M; Smith, Cheri; Trzaska, Jessica (Journal of Creativity in Mental Health, 2012)
Creative approaches to counseling help counselors to meet the needs of diverse populations. The utility of photography in counseling has been demonstrated through several case studies; however, clear implications of how photography relates to the counseling process have not been well delineated. The existing literature on phototherapy is reviewed and connected to specific photo directives within the counseling process and common psychotherapeutic techniques. © 2012 Copyright Taylor & Francis Group, LLC.
30 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/152-475-270-839-262 tex.type: [object Object]
Keywords: counseling; creative counseling; dept.csp; photography; phototherapy

The church, the closet, and the couch: the counselor's role in assisting clients to integrate their sexual orientation and religious identity - Ginicola, Misty M; Smith, Cheri (Journal of Lgbt Issues in Counseling, 2011)
In a recent article in The New York Times, therapy using Sexual Orientation Management was highlighted, with the focus on therapists assisting clients to live a heterosexual life because of their religious beliefs.The primary reasons for such an approach are to allow for client choice and respect on an equally important area of diversity, their religious affiliation and values.Although research has been performed on the intersection of religion and sexual orientation, there has not been an extensive analysis or criticism of this management technique.In this article, the authors explore the experience of religious clients struggling with their sexual orientation, discuss the potential counselor responses to sexual orientation religious issues, and the impact of each on the counseling field using ethical principles, existing research, and logical outcomes.© 2011 Copyright Taylor and Francis Group, LLC.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/028-726-215-838-214 tex.type: [object Object]
Keywords: LGBQ; counseling; dept.csp; ethics; religion

Voices from the desks: exploring student experiences in counselor education - Foss-Kelly, Louisa L.; Protivnak, Jake J. (The Journal of Counselor Preparation and Supervision, 2017)
The purpose of the qualitative study was to explore the themes that counselor education master’s students perceived as impacting their experience within a counseling program. Counselor education master’s students provided their perceptions of what they attributed to helping or hindering their progress. Themes identified as impacting their experiences were academic environment, finances, job preparation, self-care, life role balance, support, mentoring and advising, and personal growth. Recommendations are provided for counselor educators to consider when structuring programs and interacting with master’s students.
5 citations (Crossref) [2023-10-31]
Keywords: dept.csp

School Counseling Programs Identifying Academic Development Needs - Parzych, Jennifer L.; Generali, Margaret; Yavuz, Olcay (Journal of Education, 2021)
This study examined student, parent, and faculty perceptions of academic development needs and related comprehensive school counseling program services from four urban middle and high schools. Participants (n = 1,032) completed a survey designed to assist schools in planning and evaluating their career and college readiness programs, and exploring perceived student support needs. Statistically significant differences were observed in stakeholder perceptions among 12 identified interventions that support improved academic development, through factorial analysis of variance (ANOVA) and pairwise comparisons analysis. Findings provide valuable information about prioritizing student academic counseling services strategically and effectively, to meet program needs of students in high-poverty schools.
1 citations (Crossref) [2023-10-31]
Keywords: academic development; college readiness; dept.csp; dept.edl; peer-reviewed; poverty; school counselors

Written emotional expression in schools: Processing psychological and emotional stress through narrative writing. - Sassu, Kari A.; Bray, Melissa A.; Gelbar, Nicholas; Kerzner, Tiffany P. (Promoting mind–body health in schools: Interventions for mental health professionals., 2020)
tex.ids: sassuWrittenEmotionalExpression2020a
Keywords: dept.csp

A systematic approach to exploring college and career readiness program needs within high-poverty urban public schools - Yavuz, Olcay; Parzych, Jennifer; Generali, Margaret (Education and Urban Society, 2019)
This quantitative correlational study was designed to investigate whether the core and enrichment college readiness program needs within high-poverty urban schools significantly varied with respect to grade level and stakeholder perceptions. Statistically significant differences were discovered in parent, student, and faculty perceptions in core and enrichment programs related to high-poverty urban school needs. The findings provide valuable information about how to design student academic and counseling services strategically and effectively to increase college and career readiness for low-income, urban students. Findings also provide effective strategies for school leaders, educators, and counselors regarding urban school college and career readiness program needs so that resources can be intentionally distributed in areas of greatest importance.
2 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000463178900001, lens.org/043-148-982-388-631, yavuzSystematicApproachExploring2019a tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: accountability; change; dept.csp; dept.edl; peer-reviewed; school improvement; school reform; urban education

Students’ perceptions of career counselling: an examination of a graduate curriculum in the United States - Lindo, Natalya A; Ceballos, Peggy L; Blalock, Sarah; Conner, Charmaine; Edwards, Josh; Spellings, Maria; Webster, Lindsay; Opiola, Kristie (British Journal of Guidance & Counselling, 2020)
Despite its importance as a core counselling competency, less attention is given to career counselling than to other counselling specialties and it is often dismissed as a non-essential category in the counselling field. Because students’ perceptions of career counselling are affected by peer and faculty attitudes it is important to examine the training needs and experiences of graduate counselling students. Therefore, in the current study we utilised a phenomenological approach to examine students’ perceptions of a career counselling curriculum, and its impact on overall views of career counselling. Analysis of in-depth interviews yielded five major themes: View of Career Counselling, Course Delivery, Theory, Application of Knowledge, and Connection between Career Counselling and Personal Counselling. © 2019 Informa UK Limited, trading as Taylor & Francis Group.
1 citations (Crossref) [2023-10-31] tex.ids: lens.org/071-399-916-740-600, lindoStudentsPerceptionsCareer2020 tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85074340531 tex.type: [object Object] type: Article
Keywords: Career counselling; career theory; counselling theory; counsellor education; dept.csp; peer-reviewed; personal counselling

Racial identity: Choices, context, and consequences - Csizmadia, Annamaria; White, Susan (Biracial families: Crossing boundaries, blending cultures, and challenging racial ideologies, 2019)
Greater public visibility, growing social acceptance, and institutional recognition have opened up the opportunity for many contemporary biracial individuals to choose from a variety of racial identity options. Although macro-level (e.g., legal) barriers have all but disappeared, microlevel challenges (e.g., multiracial microaggressions) still persist for some in the growing biracial population. Thus, it is important to understand how racial identity options are exercised differently within and across particular social contexts, and how these options in turn affect biracial individuals’ development. In this chapter, first we discuss theory and research on racial identity and identification among contemporary biracial people, followed by a brief review of work on the contextual factors that influence racial identity formation in this population. Next, we explore extant research on the association of racial identity to a host of developmental outcomes (e.g., depression, self-esteem, psychological well-being, life satisfaction). In recognition of the heterogeneous nature of the biracial population, we review, where available, research for specific biracial subgroups (e.g., Black-White, Latino-White, and Asian-White). Drawing on relevant theory and empirical findings, we will then make specific recommendations on how to support biracial children’s racial identity formation and social-emotional development and on how to enhance biracial adults’ functioning. Finally, we summarize important gaps in current research and identify needed directions for future research.
Citation Key Alias: lens.org/007-180-235-962-622
Keywords: Academic adjustment; Contextual influences; Developmental diversity; Health behaviors; Psychosocial adjustment; Racial identity; Social context; dept.csp

Perceptions of social emotional learning needs in high poverty schools - Generali, Margaret M.; Yavuz, Olcay; Parzych, Jennifer (Journal of Contemporary Administrative Science, 2018)
This paper explores the perceived social emotional learning needs of students in high poverty schools. Social emotional learning (SEL)is recognized within the literature as critical to success in school and in life. Emergingwork supports the acquisition of a SEL skillset within grades kindergarten through twelve ( K-12) schools. This survey examines the perceptions of social emotional needs as reported by students, parents and school faculty members across four different high poverty schools in the USA. Findings provide effective strategies and valuable data for school leaders, educators, and counselors in addressing the social emotional needs of urban students.
Keywords: dept.csp; dept.edl; peer-reviewed; ⛔ No DOI found

Implementing the developmental school counseling core curriculum in the classroom - Perusse, R.; Parzych, Jennifer L.; Erford, Bradley T. (Transforming the School Counseling Profession, 2018)
Transforming the way thousands of professional school counselors approach their work with students Transforming the School Counseling Profession demonstrates how to effectively implement systemic, data-driven school counseling programs.This clearly written text presents the profession in easy-to-understand language, and is illustrated with numerous applied examples, case studies, and vignettes. The 5th Edition has been updated to include all of the latest CACREP, ASCA, and ACA standards. It also now includes the DSM-5. Coverage of cultural competence has been expanded throughout the book. Also available with MyLab Counseling MyLab is the teaching and learning platform that empowers you to reach every student. By combining trusted author content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student. MyLab Counseling organizes all assignments around essential learning outcomes and the CACREP standards–enabling easy course alignment and reporting. Note: You are purchasing a standalone product; MyLab Counseling does not come packaged with this content. Students, if interested in purchasing this title with MyLab Counseling, ask your instructor to confirm the correct package ISBN and Course ID. Instructors, contact your Pearson representative for more information. If you would like to purchase both the physical text and MyLab Counseling, search for: 0134669843 / 9780134669847 Transforming the School Counseling Profession plus MyLab Counseling with Enhanced Pearson eText – Access Card Package Package consists of: 0134610598 / 9780134610597 Transforming the School Counseling Profession 0134642651 / 9780134642659 MyLab Counseling with Enhanced Pearson eText – Access Card – for Transforming the School Counseling Profession
Keywords: dept.csp

Access versus success: Services for students with disabilities in postsecondary education. - Sassu, Kari (Journal of Educational Leadership and Policy Studies, 2018)
Keywords: dept.csp; peer-reviewed; ⛔ No DOI found

Counseling strategies for empowering people living in poverty: the I‐CARE model - Foss-Kelly, Louisa L.; Generali, Margaret M.; Kress, Victoria E. (Journal of Multicultural Counseling and Development, 2017)
Poverty has an impact on mental health and the counseling process in profound ways; however, counselors may fail to recognize the importance of poverty in clients' lives. The authors propose a model to help counselors navigate the complexities of counseling clients who are living in poverty. The I-CARE Model may help counselors develop insight about personal biases, acknowledge harsh realities of poverty, remove barriers to growth, and expand on the clients' own strengths.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/133-544-051-528-154 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: I-CARE Model; counseling; counselor; counselors; dept.csp; dura mater; human; human experiment; mental health; model; poverty; socioeconomic status

Culturally responsive practice and the role of school administrators - Minkos, Marlena L.; Sassu, Kari A.; Gregory, Jess L.; Patwa, Shamim S.; Theodore, Lea A.; Femc-Bagwell, Michele (Psychology in the Schools, 2017)
In recent years, student populations within public schools in the United States have become increasingly diverse, both culturally and linguistically, and are projected to continue to grow in diversity in the future. Consequently, educators must be prepared to support the needs and education of students with multicultural backgrounds who may differ from them. School administrators play an important role in creating safe, accepting school environments and guiding the education of diverse student populations. However, there is a need for additional guidance for school leaders in cultivating schools that promote equity for all students. Using the National Policy Board for Educational Administration (NPBEA) Professional Standards for Educational Leaders as a guiding framework, this paper provides practical suggestions regarding culturally responsive strategies and practices that school administrators might employ in leading diverse school communities.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000415935300007, lens.org/072-893-262-948-380 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: culturally responsive practice; dept.csp; dept.edl; diversity; educational leadership; peer-reviewed

Interdependent group contingency to promote physical activity in children - Foote, Catherine; Bray, Melissa A.; Kehle, Thomas J.; VanHeest, Jaci L.; Gelbar, Nicholas W.; Byer-Alcorace, Gabriel; Maykel, Cheryl; DeBiase, Emily (Canadian Journal of School Psychology, 2017)
As the number of children affected by obesity increases in the United States, it is necessary to intervene with preventive and intervention techniques that will enact change. Because children spend a significant amount of their time in school, it is of particular interest to target strategies during the school day. Given the recommendations for the total duration and intensity of physical activity children should participate in, recess period is a means of acquiring a portion of this daily recommendation. Contingent reinforcement is a technique that is consistently used in schools to promote behavior change. One of these techniques, group contingencies, has repeatedly been shown to increase desired behavior and decrease inappropriate behavior in schools. In the present study, a multiple baseline design was utilized to investigate the use of interdependent group contingencies in physical activity performance during recess, as measured by pedometers, with one class from each of the third, fourth, and fifth grades at an elementary school. Some of the variability existed in gender- and body mass index-specific (BMI) subgroups, in regard to the effectiveness of the intervention and continued maintenance of increased physical activity levels, following the removal of the intervention. However, the overall results support the use of an interdependent group contingency intervention to increase the amount of physical activity students engaged in during recess.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-793-861-482-608 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.csp; exercise; obesity; school-based treatment

Affirmative counseling with LGBTQI+ people - Ginicola, Misty M. (Amer Counseling Assn, 2017)
This current and comprehensive handbook will guide educators, students, and clinicians in developing the awareness, knowledge, and skills necessary to work effectively with LGBTQI+ populations. Twenty-five chapters written by experts in the field provide direction for working with clients in an authentic, ethical, and affirmative manner that is tailored to their individual strengths, needs, and identity. The book is divided into four sections, which explore the science behind gender and affectional orientation; developmental issues across the life span and treatment issues; the specialized needs of nine distinct populations; and the intersectionality of ethnicity and overlapping identities, the role of religion, and counselor advocacy. To further a deeper understanding of the content, each chapter contains an "Awareness of Attitudes and Beliefs Self-Check," a case narrative relating to the material covered, questions for discussion, and a list of online resources. The book concludes with an extensive glossary of terms, both preferred and problematic, which counselors working with these communities should understand and use appropriately. © 2017 by the American Counseling Association. All rights reserved.
Keywords: dept.csp

Do the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability? - Pagirsky, Matthew S.; Koriakin, Taylor A.; Avitia, Maria; Costa, Michael; Marchis, Lavinia; Maykel, Cheryl; Sassu, Kari; Bray, Melissa A.; Pan, Xingyu (Journal of Psychoeducational Assessment, 2017)
A large body of research has documented the relationship between attention-deficit hyperactivity disorder (ADHD) and reading difficulties in children; however, there have been no studies to date that have examined errors made by students with ADHD and reading difficulties. The present study sought to determine whether the kinds of achievement errors made by students diagnosed with ADHD vary as a function of their reading ability. The participants in this study were 91 students in the ADHD clinical validity standardization sample of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3), as well as a control group of 63 students selected from the larger standardization sample. Students with ADHD and reading difficulties demonstrated a statistically significant greater amount of errors across tests of academic achievement. Findings from the study are discussed within the context of past research, as well as implications for the field of school psychology and practitioners.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-372-687-541-582, pop00079 tex.type: [object Object]
Keywords: achievement; attention-deficit hyperactivity disorder; dept.csp; reading; special education

Biological gender differences in students’ errors on mathematics achievement tests - Stewart, Christie; Root, Melissa M.; Koriakin, Taylor; Choi, Dowon; Luria, Sarah R.; Bray, Melissa A.; Sassu, Kari; Maykel, Cheryl; O’Rourke, Patricia; Courville, Troy (Journal of Psychoeducational Assessment, 2017)
This study investigated developmental gender differences in mathematics achievement, using the child and adolescent portion (ages 6-19 years) of the Kaufman Test of Educational Achievement-Third Edition (KTEA-3). Participants were divided into two age categories: 6 to 11 and 12 to 19. Error categories within the Math Concepts & Applications and Math Computation subtests of the KTEA-3 were factor analyzed and revealed five error factors. Multiple ANOVA of the error factor scores showed that, across both age categories, female and male mean scores were not significantly different across four error factors: math calculation, geometric concepts, basic math concepts, and addition. They were significantly different on the complex math problems error factor, with males performing better at the p ¡ .05 significance level for the 6 to 11 age group and at the p ¡ .001 significance level for the 12 to 19 age group. Implications in light of gender stereotype threat are discussed.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-409-156-888-388, pop00119 tex.type: [object Object]
Keywords: KTEA-3; achievement; dept.csp; error analysis; factor analysis; gender; math

School counseling: Partnering with a school district to provide postsecondary opportunities for first generation, low income, and students of color - Perusse, Rachelle; Deronck, Nicole G; Parzych, Jennifer (Psychology in the Schools, 2017)
A classroom activity led by district school counselors was conducted in a K-12 school district to ensure educational equity for students in relation to postsecondary attendance. This took place in a school setting that has a large population of students of color, predominately Latino and African American students, as well as low-income students. As part of their practicum field experience, university school counseling students were supervised by school counselors at their sites to help provide a readily available and modified curriculum to instruct students about their options related to postsecondary awareness, planning, and attendance, as well as demonstrate career pathways that engender high expectations and college and career readiness. Instruction took place in the classroom as well as in small group settings.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/031-934-132-002-766 tex.type: [object Object]
Keywords: dept.csp; peer-reviewed; postsecondary opportunities